Impact of Coronavirus Disease 2019 (COVID-19) Severity on Long-term Events in United States Veterans Using the Veterans Affairs Severity Index for COVID-19 (VASIC). (5th May 2022) - Galloway, Ashley; Park, Yojin; Tanukonda, Vidisha; Ho, Yuk-Lam; Nguyen, Xuan-Mai T; Maripuri, Monika; Dey, Andrew T; Gerlovin, Hanna; Posner, Daniel; Lynch, Kristine E; Cai, Tianxi; Luoh, Shiuh-Wen; et al.
Abstract: In this retrospective cohort study of 94 595 severe acute respiratory syndrome coronavirus 2–positive cases, we developed and validated an algorithm to assess the association between coronavirus disease 2019 (COVID-19) severity and long-term complications (stroke, myocardial infarction, pulmonary embolism/deep vein thrombosis, heart failure, and mortality). COVID-19 severity was associated with a greater risk of experiencing a long-term complication 31–120 days postinfection. Most incident events occurred 31–60 days postinfection and diminished after day 91, except heart failure for severe patients and death for moderate patients, which peaked on days 91–120. Understanding the differential impact of COVID-19 severity on long-term events provides insight into possible intervention modalities and critical prevention strategies. Abstract : The Veterans Affairs Severity Index for COVID-19 (VASIC) algorithm was developed and validated on a national database. Results showed that patients experience long-term complications beyond 4 weeks postinfection and that these events increase by COVID-19 disease severity.